2004
DOI: 10.1177/08830738040190100401
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Treatments for Dyslexia: Critical Review

Abstract: The acquisition of reading is a complex neurobiologic process. Identifying the most effective instruction and remedial intervention methods for children at risk of developing reading problems and for those who are already struggling is equally complex. This article aims to provide the clinician with a review of more current findings on the prevention and remediation of reading problems in children, along with an approach to considering the diagnosis and treatment of a child with dyslexia. The first part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 38 publications
1
83
0
1
Order By: Relevance
“…Longitudinal intervention studies in different countries have demonstrated that phonological awareness training improves phonological and reading skills in novice readers, at-risk and reading disabled children (Alexander & Slinger-Constant, 2004;Ball & Blachman, 1988;Elbro & Petersen, 2004;Lundberg, Frost & Petersen, 1988;Poskiparta, Niemi & Vauras, 1999;Schneider, Kuspert, Roth, Vise & Marx, 1997;Torgesen, Morgan & Davis, 1992). The transfer effects from improved phonological skills to improved reading skills seem to be enhanced when the instruction provides explicit links between phonemes and graphemes (Bradley & Bryant, 1983;Bus & van IJzendoorn, 1999;Ehri et al, 2001;Hatcher, Hulme & Ellis, 1994;Torgesen et al, 2001;Wise, Ring & Olson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal intervention studies in different countries have demonstrated that phonological awareness training improves phonological and reading skills in novice readers, at-risk and reading disabled children (Alexander & Slinger-Constant, 2004;Ball & Blachman, 1988;Elbro & Petersen, 2004;Lundberg, Frost & Petersen, 1988;Poskiparta, Niemi & Vauras, 1999;Schneider, Kuspert, Roth, Vise & Marx, 1997;Torgesen, Morgan & Davis, 1992). The transfer effects from improved phonological skills to improved reading skills seem to be enhanced when the instruction provides explicit links between phonemes and graphemes (Bradley & Bryant, 1983;Bus & van IJzendoorn, 1999;Ehri et al, 2001;Hatcher, Hulme & Ellis, 1994;Torgesen et al, 2001;Wise, Ring & Olson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It appears these three participants were treatment resisters, which meant they did not respond or were slower to respond to interventions (Alexander & Slinger-Constant, 2004;Berninger et al, 2000;, based on their lower levels and trends for letter name and sound, words read and spelled. Empirical evidence suggests treatment resisters require differentiated instruction that meet their individual needs (Berninger et al, 2000;Alexander & SlingerConstant, 2004).…”
Section: Dysmentioning
confidence: 99%
“…Therefore, the body of research supporting multisensory structured language as efficacious for reading intervention is limited (Alexander & Slinger-Constant, 2004; and often inconclusive ). Yet parents often request it as a preferred form of reading intervention and this has led to an increase in litigation requesting multisensory instruction under the Individuals with Disabilities Education Act .…”
Section: The Impact Of Multisensory Instruction On Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetics can also help to target children most likely to profi t from interventions. Targeting is likely to be important because successful prevention programmes usually require extensive and intensive, and thus expensive, interventions (Alexander and Slinger-Constant, 2004;Hindson et al, 2005;Horowitz, 2004).…”
Section: Genetic Diagnosis Of Learning Diffi Cultiesmentioning
confidence: 99%